PENTINGNYA KONSUMSI SAYUR DAN BUAH BAGI ANAK SEKOLAH DI SDN 082/IV SIJENJANG - Arnati Wulansari; Filius Chandra (Sekolah Tinggi Ilmu Kesehatan Baiturrahim Jambi, 2019)
One of the conditions in fulfilling balanced nutrition in school children is consumption of vegetables and fruit. Consumption of vegetables and fruit can protect the body and maintain weight. However, consumption of vegetables and fruits that are less can increase the risk of chronic diseases. The aim of this community service activities was to give counseling on the importance of fruit and vegetable consumption in school children at SDN 082 / IV Sijenjang. The target in this activity is that students have good knowledge about the importance of vegetables and fruit. The output of this activity is in the form of media. The activity was held for 6 months (December 2017-May 2018) at SDN 082 / IV Sijenjang. Based on the results of community service activities there was an increase in posttest value ≥ 80 of 22.5%. The increase in the results of this knowledge must be supported by the attitude to be able to consume vegetables and fruits regularly. For this reason, it is necessary to collaborate with all parties, both from schools and health centers, to continue to improve the knowledge of SDN 082 / IV Sijenjang students so that students can implement in their daily habits.